2007
DOI: 10.1197/j.aem.2007.06.015
|View full text |Cite
|
Sign up to set email alerts
|

Closing Evidence to Practice Gaps in Emergency Care: The Australian Experience

Abstract: The National Institute of Clinical Studies (NICS) was established in 2000 by the Australian government to improve health care by closing evidence-practice gaps. Improving emergency care through use of evidence is a priority area of work for NICS. This article describes the NICS Emergency Care Program and the current application of a ''Community of Practice'' to support emergency clinicians to implement best practices research. This approach combines aspects of evidence implementation science, quality improveme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
10

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 16 publications
(16 reference statements)
0
11
0
10
Order By: Relevance
“…Participants identified that limited time, staffing and resources present in the ED hinder the opportunity emergency nurses have to learn and apply HIRAID in the clinical setting. Lack of time is commonly reported as a barrier to the uptake of research evidence into emergency nursing practice (Chan et al., ; Huckson & Davies, ). Whilst it may not be possible to change these restrictions within the ED clinical environment, a number of other strategies may be used to ensure nurses have sufficient support and opportunity to learn and apply the HIRAID assessment framework in their clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Participants identified that limited time, staffing and resources present in the ED hinder the opportunity emergency nurses have to learn and apply HIRAID in the clinical setting. Lack of time is commonly reported as a barrier to the uptake of research evidence into emergency nursing practice (Chan et al., ; Huckson & Davies, ). Whilst it may not be possible to change these restrictions within the ED clinical environment, a number of other strategies may be used to ensure nurses have sufficient support and opportunity to learn and apply the HIRAID assessment framework in their clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…5 A national initiative to implement pain management recommendations commenced in 2007. 6 The first phase of the initiative involved a national audit of ED pain management practice 7 informed by evidence approved by the National Health and Medical Research Council (NHMRC), 8 and an investigation of enablers and barriers to best-practice pain management. The second phase (2008-2010) is a national programme aiming to increase adherence to best-practice pain management in EDs.…”
Section: Introductionmentioning
confidence: 99%
“…25 The National Institute of Clinical Studies (NICS), an institute of the Australian government National Health and Medical Research Council (NHMRC), has set out to improve health care by closing evidence gaps. 26 Through the NHMRC-NICS sponsored Emergency Care Community of Practice (EC CoP), pain has been identified as a clinical priority area and current implementation initiative aim to improve evidence-based pain management.…”
Section: Introductionmentioning
confidence: 99%
“…In Australia and New Zealand, key evidence‐based documents have been developed by the Australian and New Zealand College of Anaesthetists (ANZCA) for the management of acute pain 24 and by the Royal Australasian College of Physicians (RACP) for the management of procedure‐related pain in children and adolescents 25 . The National Institute of Clinical Studies (NICS), an institute of the Australian government National Health and Medical Research Council (NHMRC), has set out to improve health care by closing evidence gaps 26 . Through the NHMRC‐NICS sponsored Emergency Care Community of Practice (EC CoP), pain has been identified as a clinical priority area and current implementation initiative aim to improve evidence‐based pain management.…”
Section: Introductionmentioning
confidence: 99%